2019
DOI: 10.4236/aim.2019.910052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CTXM, SHV, TEM AND OXA Genes among Extended-Spectrum Beta-Lactamase Producing <i>Klebsiella pneumoniae</i> from Mukuru Slum, Kenya

Abstract: Background: Extended spectrum beta lactamases (ESBLs) producing Enterobacteriaceae cause infections that are often reported in both hospital and community setting. These infections are on the increase and jeopardize the achievement of modern medicine because of their clinical implications. There is need for surveillance measures to be taken, both by the health care personnel and the community at large. Methodology: We examined 330 diarrhea stool samples from children below the age of 5 years and processed them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…These are from hospitals in three Kenyan counties: Nairobi, Kiambu, and Kilifi. With increasing carbapenem use in Kenya because of the high levels of ESBL-producing Enterobacteriaceae [ 27 29 ], a concomitant rise in CR is expected that warrants close monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…These are from hospitals in three Kenyan counties: Nairobi, Kiambu, and Kilifi. With increasing carbapenem use in Kenya because of the high levels of ESBL-producing Enterobacteriaceae [ 27 29 ], a concomitant rise in CR is expected that warrants close monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of more than one beta-lactamase in one bacterial isolate has been reported in humans. For instance, in Kenya, a double combination of CTX-M/TEM and CTX-M/SHV and a triple combination of CTX-M/SHV/TEM was noted by Saisi et al (2019) from diarrhea stool samples from children. Mshana et al (2013) reported a combination of CTX-M/TEM, SHV/CTX-M, and CTX-M alone in neonatal sepsis in Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction for amplification of bla TEM , bla CTX-M , bla SHV, bla OXA-1, and bla KPC genes Amplification was performed in 10 µl reaction mixture containing 2 µl of 5X FIREPol Master Mix containing FIREPol DNA polymerase (Solis BioDyne, Tartu, Estonia), 0.5 µl of 10 pmol/ µl of the primers (Macrogen, Europe), and 4 µl of template DNA as described by Saisi et al (2019) with modifications. The polymerase chain reaction (PCR) water was used to top up the reaction volume to 10 µl.…”
Section: Primer Propertiesmentioning
confidence: 99%
See 2 more Smart Citations